Zinc Doping Enhances the Electrocatalytic Properties of Cobalt Borides for the Hydrogen Evolution Reaction - Quílez-Bermejo, Javier; García-Dalí, Sergio; Karthik, Raj; Canevesi, Rafael; Izquierdo, María T.; Emo, Mélanie; Celzard, Alain; Fierro, Vanessa (Frontiers in Energy Research, 2022)
Electrochemical water splitting requires new, low-cost cathode electrodes for the hydrogen evolution reaction to enable the worldwide implementation of electrolyzers. Cobalt borides are proposed as one of the most promising materials to overcome the limitations of the commercial electrocatalysts, but the catalytic activity still needs to be improved to be competitive. Here, we report that the introduction of zinc into cobalt boride to produce ternary cobalt boride is an efficient route to further improve the catalytic activity towards the hydrogen evolution reaction (HER) of cobalt boride. The ternary Co-Zn-B was prepared by an easy chemical reduction method to achieve superior HER electrocatalytic performance with a lower overpotential than the homologous Co-B. The larger surface area, structural order, crystallization degree and, in particular, the different surface chemistry seem to be key factors for this improvement.